Fasilitas Komunitas Sepeda Di Pekanbaru Dengan Pendekatan Arsitektur Ekspresionis - Herliman Restu Waruwu; Pedia Aldy; Mira Dharma Susilawaty (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Bicycle community facilities is a place for bicycle community located in city of Pekanbaru. The growth of the bicycle community in Pekanbaru is a form of passion arising from the user of the bicycle itself, such as the desire to strengthen friendship between bicycle enthusiasts, socialize, cultivate confidence Different in the environment and channeling the talent, cultivating a healthy lifestyle, and also to participate in events held by the Department of Pekanbaru. With so many communities and events for bicycle users, there is an idea to host bicycle users. The facilities are hosted by communal outdoor and Indoor areas, outdoor stage, BMX outdoor area, garden, bicycle retail, bicycle workshop, Mini Gallery, Minimarket, café and other functions related to bicycle users. The Study method used is an expressionist architecture approach, which is to apply the principles and design ideas. The concept applied is a transformation concept of bicycle movement called "Backlash" which is a manufer movement in cycling. With an expressive look of the movement of the bicycle is expected to be integrated between the architecture and the user, thus producing a new place for the bicycle user community in the city of Pekanbaru..Keywords : Expressionist architecture, community, bicycles, Pekanbaru